Cell-Mediated Branch Fusion in the Drosophila Trachea. - Jiang, L. (Results and Problems in Cell Differentiation, 2024)
The Drosophila trachea is an interconnected network of epithelial tubes, which delivers gases throughout the entire organism. It is the premier model to study the development of tubular organs, such as the human lung, kidney, and blood vessels. The Drosophila embryonic trachea derives from a series of segmentally repeated clusters. The tracheal precursor cells in each cluster migrate out in a stereotyped pattern to form primary branches. Thereafter, the neighboring branches need to fuse to form an interconnected tubular network. The connection between neighboring branches is orchestrated by specialized cells, called fusion cells. These cells fuse with their counterparts to form a tube with a contiguous lumen. Branch fusion is a multi-step process that includes cell migration, cell adhesion, cytoskeleton track formation, vesicle trafficking, membrane fusion, and lumen formation. This review summarizes the current knowledge on fusion process in the Drosophila trachea. These mechanisms will greatly contribute to our understanding of branch fusion in mammalian systems.